Automation of Cost Recovery in the public health system of the Autonomous City of Buenos Aires - Guerrero Giménez, María Luz (2025)
In Argentina, the health system operates under a mixed and decentralized model, combining different levels of management and financing. Within this framework, the cost recovery process in the public health sector of Buenos Aires City (CABA), regulated by Law 5.622 and its amendments, aims to recover the costs of health services provided to patients with insurance coverage. Following the implementation of the Electronic Health Record (EHR) system and the progressive digitalization of clinical data, the Health Information and Statistics Management Office (GOGIES) launched a document automation project to improve compliance with administrative procedures. As the system became more complex and data volume increased, it was necessary to redesign document generation processes. The proposed solution focused on building workflows based on Directed Acyclic Graphs (DAGs), using open-source tools such as R and GO. This enabled greater computational efficiency, scalability of report generation, and timely availability of documents for billing purposes.